Domestic violence and the infractional act: Perceptions of adolescents serving socio-educational internment measures - Kalume, Sabrina Mamede Napoleão (2025)
This study aimed to analyze the perceptions of adolescents serving socio-educational measures about domestic violence and the criminal act. This is a documentary study, with a qualitative-quantitative, exploratory and descriptive approach, applying the categorization and frequency techniques of Content Analysis. Thirty reports of adolescent boys, made available by the Socio-Educational Assistance Foundation, through the Male Socio-Educational Units, Uase/IMA I, from 2020 to 2023, were analyzed through content analysis. The results show that 40% of the adolescents have no contact with their father; 23.30% do not know him and 6.60% indicated that the father/parent was in prison; 26.60% have a conflictual relationship with their mother. In 2 cases of drug-dealing brothers, who passed through the socio-educational measures system, in addition to 2 others who were murdered. Regarding reports of physical violence, it was found that the presence of physical violence (f=7), with the aggressors being the stepfather (f=3) and the father-parent/adoptive father (f=3). In the 8 cases of intrafamily violence, there was a dysfunctional family context and in 5 of them the category of social vulnerability. Based on the results obtained, it is clear that there is an urgent need for debate and expansion of actions that guarantee the safety and well-being of children and adolescents within the intrafamily environment. In addition, the lack of diagnosis and specific data on intrafamily violence also hinders the deepening of the subject and limits the research, making it necessary to investigate the characteristics of the perpetrators and the associated factors.